2020
DOI: 10.1111/aej.12476
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of true vertical root fracture line in endodontically treated teeth using a new subtraction software – A Micro‐CT and CBCT study

Abstract: This study aimed to find true facture lines in endodontically treated teeth on CBCT images using digital subtraction and to evaluate the influence of width of facture lines in the diagnosis. Thirty‐two endodontically treated teeth with vertical root fractures (VRFs) from 30 patients were included in this study. The CBCT images of the patients and the micro‐CT images of extracted teeth were imported into our digital subtraction software to distinguish the true facture lines from the streak artefacts. Of them, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“… 28 34 In vivo studies have shown that early root fracture lines can be quite subtle. 6 35 36 The lack of studies exclusively focused on incomplete fractures, as well as the in vitro nature of the present study, limits the results available for comparison.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“… 28 34 In vivo studies have shown that early root fracture lines can be quite subtle. 6 35 36 The lack of studies exclusively focused on incomplete fractures, as well as the in vitro nature of the present study, limits the results available for comparison.…”
Section: Discussionmentioning
confidence: 98%
“… 11 20 The present results indicate that the use of the MAR algorithm in unfilled teeth improved the diagnosis rate of incomplete VRF, in accordance with several previous studies. 1 6 8 21 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 Compared to CBCT, micro-CT has smaller voxel sizes and a longer exposure, enabling the detection of more subtle and smaller changes. 14 Quantitative gray value measurements in CBCT, in contrast to micro-CT, are unreliable and therefore should generally be avoided. Because of the geometry of the beam and flat-panel detectors, artifacts, and variation in scanning circumstances, CBCT-based density measurements are inevitably erroneous.…”
Section: Introductionmentioning
confidence: 99%